Politeness Strategies in Teaching English At SMP Advent 2 Medan - Kaban, Misnarianita; Sinaga, Nenni Triana; Tampubolon, Sahlan (ALACRITY : Journal of Education, 2024)
This study focused on analyzing the teacher's utterances, namely, there are types of Politeness strategies by Yule's theory (1996), which researchers took to be two strategies, namely positive politeness and negative politeness. This research uses the descriptive-qualitative method by conducting observation and documentation. Based on the results of the analysis applied, researchers found 42 pieces of data from both types, namely positive politeness and negative politeness. Positive politeness: there are 29 data points with a percentage of 69% and negative politeness: there are 13 data points with a percentage of 31%. From the results of this study, the most dominant thing teachers say when teaching is that teachers apply positive politeness. This analysis shows how important politeness strategies are to improving teacher-student interaction. It shows that a balanced approach can help the teaching and learning process be better and students feel motivated.